Post-Thermal Performance of Concrete Containing 60% of Slag - Khindir, Qurratuaini; Zuhan, Nurizaty; Oh , Chai Lian; Kado, Bishir (International Journal of Integrated Engineering, 2025)
Post-thermal performances of concrete have been studied extensively, as it is crucial to determine whether the structure can be used after a fire event; however, concrete properties can always be improved. One of the innovations introduced in concrete mixtures is the replacement of cement with industrial waste materials, such as slag. Concrete containing slag is already established in the construction industry. However, there is limited information regarding the post-thermal performance of concrete containing slag up to a 60% replacement. Hence, this study aims to investigate the post-thermal performance of concrete containing 60% slag replacement at ambient temperature and after exposure to elevated temperatures of 200°C and 500°C for one hour. Therefore, the properties of hardened concrete were determined. Three batches of 100 mm ´ 100 mm ´ 100 mm cubes specimens containing 0% (normal concrete, NC) and 60% slag replacement (concrete containing slag, CCS) were tested under compressive strength test. It was found that the compressive strength of CCS is 34.4 MPa, which is lower than that of NC, which achieved 40.6 MPa with 0.85 difference ratio. The residual compressive strength of CCS is 32.6 MPa, while NC has 47.4 MPa, with 0.69 difference ratio. The residual compressive strength decreases gradually with an increasing temperature exposure up to 500°C. A similar trend also occurs on modulus of elasticity (MOE); CCS has a decrease of elastic modulus compared to NC. In contrast for 200°C temperature exposure, CCS shows an increment about 19 on MOE value. However, both NC and CCS maintain a residual compressive strength exceeding 30 MPa, which remains within the acceptable target range. It can be concluded that slag can give an acceptable potential for the future in construction industry.